2019
DOI: 10.1002/smr.2165
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of effort estimation supported by change impact analysis in agile software development

Abstract: In agile software development, functionality is added to the system in an incremental and iterative manner. Practitioners often rely on expert judgment to estimate the effort in this context. However, the impact of a change on the existing system can provide objective information to practitioners to arrive at an informed estimate. In this regard, we have developed a hybrid method, that utilizes change impact analysis information for improving effort estimation. We also developed an estimation model based on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
3
0
4
Order By: Relevance
“…Assim, o estudo de Tahir, Rasool e Noman (2018) apresentou que 51% dos modelos de medição são referentes a melhoria de processo de software, 60% sobre uso de especialistas em medição e experiência, 40% sobre o uso de padrões de medição e 22% sobre o uso de ferramentas automatizadas. Tanveer et al (2019) desenvolveram um método híbrido que utiliza informações de análise de impacto de mudança na estimativa de esforço e do modelo de estimação baseado em árvores impulsionadas por gradiente (AIG). A avaliação subjetiva de Tanveer et al (2019) sobre o Hybrid Effort Estimation in Agile Software Development (HyEEASe) e do Planning Poker (PK) foi sobre medir a facilidade de uso percebida, utilidade e aprendizagem.…”
Section: Métricas áGeis De Produtounclassified
“…Assim, o estudo de Tahir, Rasool e Noman (2018) apresentou que 51% dos modelos de medição são referentes a melhoria de processo de software, 60% sobre uso de especialistas em medição e experiência, 40% sobre o uso de padrões de medição e 22% sobre o uso de ferramentas automatizadas. Tanveer et al (2019) desenvolveram um método híbrido que utiliza informações de análise de impacto de mudança na estimativa de esforço e do modelo de estimação baseado em árvores impulsionadas por gradiente (AIG). A avaliação subjetiva de Tanveer et al (2019) sobre o Hybrid Effort Estimation in Agile Software Development (HyEEASe) e do Planning Poker (PK) foi sobre medir a facilidade de uso percebida, utilidade e aprendizagem.…”
Section: Métricas áGeis De Produtounclassified
“…However, the absence of the developer's experience, prior team knowledge, and technical complexity negatively impacts on estimation accuracy. Later, Tanveer et al [20] updated their previously developed Gradient boosted tree and compared their results with their predictions-based model. The authors evaluated the usefulness and effectiveness of their proposed model with an agile team effort estimation.…”
Section: Related Workmentioning
confidence: 99%
“…In comparison to [19,20], Conoscenti et al [21] identified the underlying reasons for inaccurate estimation and incorporated software project data analytics with development teams. After identifying the causes of inaccurate estimations, the authors used an interactive visualization tool highlighting actual and estimated effort levels based on the developer's feedback.…”
Section: Related Workmentioning
confidence: 99%
“…Although there are many published papers with increasingly sophisticated algorithms to creating finer duration estimates in the PM literature, these either assume the data are available or acknowledge that such estimation may be difficult even with data, for example where different scales are used in varied contexts (Jovanovi c et al, 2017, p. 185). However, traditional development approaches focused on input and output can address these issues, but AI and analytics may extend estimation in new directions, for example, estimating the impacts such as cost, delay or risks in evaluating change requests (Tanveer et al, 2019).…”
Section: Duration Estimatesmentioning
confidence: 99%